The National Film Industry as a Component of National Identity and Nation Branding - Holma, Minttu (My University, 2024)
Movies are a significant part of popular culture. They can be effective in communicating aspects of a nation through their audiovisual and story-driven nature. This both connects the nation internally and spreads the narrative across borders. From a nation branding perspective, movies can be a valuable asset if used correctly because they are a widespread form of media and easily approachable. The main research questions that this thesis aims to answer is how a national film industry contributes to a country’s national brand, and, further, how it can bridge the gap between nation branding and national identity. The findings of this thesis conclude that nations can use movies to effectively communicate five dimensions of their brand: people, environment, culture, history, and politics. Emotionally charged pieces of media, such as movies, offer viewers relatable characters, engaging stories, and new points of view. As transportation theory suggests, the more immersed a viewer is, the easier it is for the story to alter their attitudes, ideas, and values. Additionally, it has been found that the piece of media does not necessarily need to elicit positive emotions for the acceptance of presented attitudes to take place. This also supports the notion that movies are effective tools of nation branding.

Elokuvat ovat keskeinen osa populaarikulttuuria. Niiden audiovisuaalinen ja tarinakeskeinen luonne voi tehdä niistä tehokkaita kansakunnan eri osa-alueiden näyttämisessä, mikä sekä yhdistää kansaa, että jakaa tietoa muihin maihin. Kansallisen brändäyksen näkökulmasta elokuvat voivat olla oikein käytettynä tehokas työkalu, sillä ne ovat helposti lähestyttäviä ja nykyteknologian ansiosta saatavilla laajoille yleisöille. Tämä tutkielma pyrkii vastaamaan siihen, miten kansallinen elokuvateollisuus osallistuu kansallisen brändin rakentamiseen, ja miten se yhdistää kansallisen brändäyksen ja kansallisidentiteetin. Tutkimustulokset osoittavat, että elokuvissa välittyy viisi eri kansakunnan osa-aluetta: ihmiset, ympäristö, kulttuuri, historia ja politiikka. Tunnepitoiset elokuvat tarjoavat katsojille samaistuttavia hahmoja, mielenkiintoisia tarinoita ja uusia näkökulmia. Transportaatioteorian mukaan tarinassa esitetyt asenteet, ideat ja arvot omaksutaan helpommin, kun tarinan kokija eläytyy siihen vahvasti. Nykyisen tutkimustiedon valossa näyttää myös siltä, että tarinan herättämien tunteiden ei tarvitse olla välttämättä positiivisia haluttujen asenteiden välittymiseksi. Myös tämä tukee elokuvien tehokkuutta kansallisen brändäyksen työkaluina.
Keywords: nation branding, national identity, national cinema, popular culture